Pengembangan Bahan Ajar Matematika Untuk Mendukung Pembelajaran Berdiferensiasi Di Sekolah Dasar - Hayati, Neng Aat; Alamsyah, Trian Pamungkas; Pamungkas, Aan Subhan (Journal Mathematics Education Sigma [JMES], 2024)
The aim of this research is to describe the development of mathematics teaching materials in the form of block and cube learning modules that support differentiated learning. Apart from that, to describe the suitability of teaching materials and students' responses to teaching materials. This type of research uses research and development (RD) with the five steps of the ADDIE development model (analysis, design, development, implementation and evaluation) used in development research. The final product is a learning module in the form of blocks and cubes which is used as a tool in differentiated learning. Expert validation assessment shows the feasibility of teaching material products. The assessment includes: a) validation from two media experts who obtained a score percentage of 85% with the interpretation "very appropriate"; b) validation from two material experts obtained a score percentage of 93.75% with the interpretation "very feasible"; and c) validation from two language experts who obtained a score percentage of 97.75% with a "very appropriate" interpretation. Students' responses to the use of block and cube learning modules as teaching aids to support differentiated learning obtained a percentage of 88.63% with the interpretation "very good". Based on the research results, it can be concluded that the development of teaching materials in the form of block and cube learning modules to support differentiated learning in class IV elementary school is very valid and practical.